APLIKASI INVERS GRUP PADA KARAKTERISASI INVERS MOORE PENROSE - SRRM, Titi Udjiani (MATEMATIKA, 2016)
Let  be a ring with identity and equipped with  involution " ". If  is element of  and has the Moore Penrose inverse, then  and  also have the  Moore Penrose inverse. This paper  found thatMoore Penrose inverse of is the same with the group inverse of   Also the Moore Penrose inverse of  is the same with the group inverse of Then the results of this  investigation  are  used to   discusse the characteristic of the Moore Penrose inverse of elements in  through the group inverse .